The Effect of Psychomotor Performance, Cerebral and Arterial Blood Saturation between African-American and Caucasian Males Before, During and After Normobaric Hypoxic Exercise - FEEBACK, MATTHEW R. (Int J Exerc Sci, 2017)
To further elucidate physiological and cognitive performance differences between African-American (AA) and Caucasian individuals (CAU) before, during or after hypoxic and normoxic exercise. Twelve college aged (18–25) apparently healthy African-American (six volunteers) and Caucasian (six subjects) males took part in two trials consisting of normobaric normoxia and normobaric hypoxia (12% oxygen). Each subject cycled at 50% of their altitude adjusted VO(2max) (−26% of normoxia VO(2max)) for one hour after a two-hour baseline. Subjects were monitored for cerebral and arterial O(2) saturation, as well as the Trail Making Test A and B (TMT) psychomotor performance. Arterial saturation proved to be significantly higher in AA (86.0±4.7) compared to CAU (79.5±4.8) during the first 60 minutes of exposure to hypoxia at rest (p=0.039), but not during exercise. However, cerebral oxygenation to the left frontal lobe was decreased near the conclusion and in 30 minutes after normoxic exercise. TMT B data revealed that CAU (79±12.7) had faster scores than the AA subjects (98±25.1) at all time points and was significantly different at the 115-minute time point of the hypoxic trial (p=0.024). The data suggests that before, during and after normobaric normoxia and hypoxia trial there is a differential response between AA and CAU in regards to arterial and cerebral oxygenation, as well as psychomotor tests.